2017
DOI: 10.1128/iai.00948-16
|View full text |Cite
|
Sign up to set email alerts
|

Giardia Alters Commensal Microbial Diversity throughout the Murine Gut

Abstract: Giardia lamblia is the most frequently identified protozoan cause of intestinal infection. Over 200 million people are estimated to have acute or chronic giardiasis, with infection rates approaching 90% in areas where Giardia is endemic. Despite its significance in global health, the mechanisms of pathogenesis associated with giardiasis remain unclear, as the parasite neither produces a known toxin nor induces a robust inflammatory response. Giardia colonization and proliferation in the small intestine of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 102 publications
(140 reference statements)
5
111
2
Order By: Relevance
“…Since microbiota were shown to influence the outcome of infection, our lab and the Dawson group conducted the first culture-independent assessment of the intestinal microbiota during Giardia infections and found that infections influence both the architecture and abundance of the intestinal microbiota in the small intestine [37]. While this report emphasizes data using Giardia -infected mice that were pre-treated with antibiotics, and although antibiotic treatment itself causes a shift in the microbiota composition, the overall shift in microbial ecology was still present in infected mice that had not been treated with antibiotics.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
See 3 more Smart Citations
“…Since microbiota were shown to influence the outcome of infection, our lab and the Dawson group conducted the first culture-independent assessment of the intestinal microbiota during Giardia infections and found that infections influence both the architecture and abundance of the intestinal microbiota in the small intestine [37]. While this report emphasizes data using Giardia -infected mice that were pre-treated with antibiotics, and although antibiotic treatment itself causes a shift in the microbiota composition, the overall shift in microbial ecology was still present in infected mice that had not been treated with antibiotics.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
“…While this report emphasizes data using Giardia -infected mice that were pre-treated with antibiotics, and although antibiotic treatment itself causes a shift in the microbiota composition, the overall shift in microbial ecology was still present in infected mice that had not been treated with antibiotics. A decrease in the diversity and abundance of the obligate anaerobic Firimicutes taxa occurred, while an increase in the diversity of the taxa of aerobic Rhodocyclaceae, Moraxellaceae , Flavobacteriales , and Comomonadaceae was reported [37]. These enriched taxa are all considered to be metabolically flexible, and prosper with increased oxygen tension, lipid availability, and competition for arginine.…”
Section: Giardia Interactions With Intestinal Commensal Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…Although some cross-domain research aims to gain closer insight into apparently pathogenic protists (e.g. Giardia) and their relationships with bacterial microbiota in producing host disease (Barash et al 2017), many studies explore more positive interactions. In many such cross-domain analyses, distribution patterns are used to formulate hypotheses about the evolved nature of these interactions, such as the lower abundances of fungi being seen as a "reservoir" for certain functional interactions in particular contexts (Huffnagle and Noverr 2013).…”
Section: Cross-domain Relationships and Their Implicationsmentioning
confidence: 99%